2013
DOI: 10.1371/journal.pone.0075817
|View full text |Cite
|
Sign up to set email alerts
|

A Tuneable Switch for Controlling Environmental Degradation of Bioplastics: Addition of Isothiazolinone to Polyhydroxyalkanoates

Abstract: Controlling the environmental degradation of polyhydroxybutyrate (PHB) and polyhydroxyvalerate (P(HB-co-HV)) bioplastics would expand the range of their potential applications. Combining PHB and P(HB-co-HV) films with the anti-fouling agent 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one (DCOI, <10% w/w) restricted microbial colonisation in soil, but did not significantly affect melting temperature or the tensile strength of films. DCOI films showed reduced biofouling and postponed the onset of weight loss by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For example, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one (DCOI) is an anti-fouling agent, which is known to inhibit the onset of PHB and PHBV biodegradation according to ASTM D5988. 196 The chain extender Joncryl ADR-4368-CS had a similar inhibitory effect on the onset of PHA biodegradation, despite it being reported to reduce the crystallinity of PHAs, which should improve the biodegradation 197 at loadings of 5%, the Joncryl chain extender reduced the extent of soil biodegradation from 70 to 22% in 340 days following the ASTM D5988-03 protocol. The inhibitory effect is also seen under composting conditions and marine conditions at 0.2 and 5% loadings, negatively impacting the biodegradation start time, rate and extent.…”
Section: Chemical Additives and Blending Effect On Pha Biodegradationmentioning
confidence: 95%
“…For example, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one (DCOI) is an anti-fouling agent, which is known to inhibit the onset of PHB and PHBV biodegradation according to ASTM D5988. 196 The chain extender Joncryl ADR-4368-CS had a similar inhibitory effect on the onset of PHA biodegradation, despite it being reported to reduce the crystallinity of PHAs, which should improve the biodegradation 197 at loadings of 5%, the Joncryl chain extender reduced the extent of soil biodegradation from 70 to 22% in 340 days following the ASTM D5988-03 protocol. The inhibitory effect is also seen under composting conditions and marine conditions at 0.2 and 5% loadings, negatively impacting the biodegradation start time, rate and extent.…”
Section: Chemical Additives and Blending Effect On Pha Biodegradationmentioning
confidence: 95%
“…Moreover, as estimated, the complete degradation of the films in a soil mixture at 50 °C would take approximately 453 days, assuming the zeroth-order kinetics for the degradation. For comparison, it has been previously demonstrated that the PHB films were degraded with 95% mass loss after 35 days in field soil at 28 °C with 50% moisture and 58% mass loss after 160 days in sea. , …”
Section: Resultsmentioning
confidence: 99%
“…Environmental degradation of the bioplastics samples was conducted in "mature soil" under controlled conditions (Woolnough et al, 2013).…”
Section: Influence Of Soil Type On the Degradation Ratementioning
confidence: 99%